2007
DOI: 10.3390/12092215
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Spiroannulation of Phenolic Substrates: Advances Towards the Asymmetric Formation of the Manumycin m-C7N Core Skeleton

Abstract: Abstract:The asymmetric syntheses of two new spirolactones prepared in optically pure form from L-3-nitrotyrosine are described. The key step, an oxidative spiroannulation, was carried out on the optically active phenols 11a and 11b and afforded the new spirolactones 5a and 5b in 85% and 83% yields, respectively, as mixtures (3:1 dr) of diastereomers. The major diastereomers from these mixtures could be isolated in optically pure form by trituration using acetone-hexanes as the solvent. Thus, the optically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…With the desired monoprotected resorcinol tyrosine analogue in hand, we were poised to test the oxidative dearomatization of the dissymmetric resorcinol 8. 9 We hoped that the methoxy and amine residues would emerge being positioned on opposite sides of the conjoined spirocyclic molecule in a diastereoselective manner, reminiscent of a reaction developed by Wardrop et al. for the production of spiroamides from nitrenes 10.…”
Section: Methodsmentioning
confidence: 99%
“…With the desired monoprotected resorcinol tyrosine analogue in hand, we were poised to test the oxidative dearomatization of the dissymmetric resorcinol 8. 9 We hoped that the methoxy and amine residues would emerge being positioned on opposite sides of the conjoined spirocyclic molecule in a diastereoselective manner, reminiscent of a reaction developed by Wardrop et al. for the production of spiroamides from nitrenes 10.…”
Section: Methodsmentioning
confidence: 99%
“…2003c). Other studies have also shown the importance of the presence of electron donating groups (EDG) such as methoxy or amide ortho to the phenolic hydroxyl as shown in compounds 1-3 in Figure 1 (Plourde et al, 2005;Plourde et al, 2007;Plourde et al, 2008). Such groups not only increase the overall chemical yield of the spiroannulation reaction, but also appear to favour a higher diastereoselectivity as well.…”
Section: Introductionmentioning
confidence: 99%
“…With the desired monoprotected resorcinol tyrosine analogue in hand, we were poised to test the oxidative dearomatization of the dissymmetric resorcinol. [8,9] We hoped that the methoxy and amine residues would emerge being positioned on opposite sides of the conjoined spirocyclic molecule in a diastereoselective manner, reminiscent of a reaction developed by Wardrop et al for the production of spiroamides from nitrenes. [10] To our delight, sequential exposure of the acid 5 to hypervalent iodine and DBN provided the spirocyclic lactone 4 as the major diastereomer (61 % overall yield, > 12:1 d.r.…”
mentioning
confidence: 99%